Hotel Risk Management Implementation Based on Technology over LH Hotel - Rona Novia; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Journal of Multidisciplinary Academic, 2020)
The current economic growth encourages many businesses to grow and thrive. The one of them is growing is Hotel in Bekasi city. The realization of investment in Bekasi City reached 17 trillion IDR over 2017. Thus, the investment targets to encouraged businesses to grow such as business developers in hotels and apartments building over the Bekasi area reached 17 trillion IDR. The increasing factor also needs balanced with the increased availability of hotel rooms and accommodations so that does not create a gap between demand and supply for hotel rooms or accommodations. Business growth and development needs must be planned so that the business can continue running. One of the things must be considered is the risk management, so every business can find out which factors must be considered in developing its business itself.